Integrasi Nilai-Nilai Islam dalam Pembangunan Berkelanjutan Melalui Program Corporate Social Responsibility - Saputra, Devid (IAIN PONOROGO, 2025)
This study discusses the importance of integrating Islamic values ​​in implementing Corporate Social Responsibility (CSR) programs to support sustainable development in Indonesia. Islamic values ​​such as justice, balance, social responsibility, and concern for the environment are a strong ethical foundation for directing CSR so that it not only focuses on economic aspects, but also pays attention to social welfare and environmental sustainability. This approach is in line with the principle of maqasid sharia, which emphasizes the welfare of the community, so that CSR based on Islamic values ​​can be a model of inclusive and sustainable development. However, there are challenges such as business actors'business actors' lack of understanding and capacity to implementto implement these values ​​effectively. Therefore, strengthening policies, training, and developing CSR models based on Islamic values ​​is very much needed. In addition, multi-stakeholder collaboration and monitoring mechanisms that refer to Islamic values ​​are the keys to successfully implementing sustainable CSR. The integration of Islamic values ​​in CSR not only strengthens the moral and social foundations in business practices but also makes a significant contribution to equitable social, economic, and environmental development in Indonesia.